频谱函数F (jω)=δ(ω-2)+δ(ω+2)的傅里叶逆变换f (t) = ______
举一反三
- 频谱函数F(jω)=的傅里叶反变换f(t)=_。 A: ε(t) B: ε(t) C: u(t) D: u(t)
- 频谱函数F(jw)=的傅里叶逆变换f(t)等于() A: -ε(-t) B: ε(t) C: -ε(-t) D: ε(t)
- 函数F(jω)=2cos(3ω)的傅里叶逆变换为( )。 A: 2[δ(t+3)+δ(t-3)] B: δ(t+3)+δ(t-3) C: 2[δ(t+3)-δ(t-3)] D: δ(t+3)-δ(t-3)
- 傅里叶逆变换的公式为() A: f(t)=; B: f(t)=; C: f(t)=; D: f(t)=。
- 频谱函数F(jω)=2u(1−ω)的傅里叶逆变换f(t)= _____。 A: [img=86x39]18034ef63cec38f.png[/img] B: [img=91x41]18034ef64532a69.png[/img] C: [img=92x41]18034ef64dc2d20.png[/img] D: [img=98x39]18034ef65702c7b.png[/img]